2008
DOI: 10.1590/s0100-879x2008005000023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the time-of-day of training on explicit memory

Abstract: Studies have shown a time-of-day of training effect on long-term explicit memory with a greater effect being shown in the afternoon than in the morning. However, these studies did not control the chronotype variable. Therefore, the purpose of this study was to assess if the time-of-day effect on explicit memory would continue if this variable were controlled, in addition to identifying the occurrence of a possible synchronic effect. A total of 68 undergraduates were classified as morning, intermediate, or afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 21 publications
3
18
0
1
Order By: Relevance
“…However, our findings are consistent with previous results showing that the time of retrieval (morning/evening) did not affect the current memory performance (e.g. Barbosa & Albuquerque, 2008;Folkard & Monk, 1978;Gais et al, 2006). Although the time of reactivation of the events (morning vs. evening) had no effect on the number of recorded events in the first phase of the experiment, the time of recording had a significant influence on the long-term accessibility of the reactivated memories.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…However, our findings are consistent with previous results showing that the time of retrieval (morning/evening) did not affect the current memory performance (e.g. Barbosa & Albuquerque, 2008;Folkard & Monk, 1978;Gais et al, 2006). Although the time of reactivation of the events (morning vs. evening) had no effect on the number of recorded events in the first phase of the experiment, the time of recording had a significant influence on the long-term accessibility of the reactivated memories.…”
Section: Discussionsupporting
confidence: 93%
“…Folkard and Monk (1978) as well as Barbosa and Albuquerque (2008), Gais, Lucas and Born (2006) also found that only the time of learning influenced the longterm recall performance in a group of high school students, but the time of testing had no effect on later memory. Authors argued that a possible explanation of better memory for materials learnt in the evening could be that learning in the evening is usually followed by sleeping.…”
Section: A Diary After Dinner: How the Time Of Initial Retrieval Inflmentioning
confidence: 94%
See 2 more Smart Citations
“…Based on the results of the questionnaire, subjects are divided into five different categories: extreme morning type, moderate morning type, intermediate type, moderate afternoon type, and extreme afternoon type. Barbosa and Albuquerque (2008), Kim, Dueker, Hasher, and Goldstein (2002), and May and Hasher (1998) have suggested that the chronotype of a subject may change over the course of life and studies indicate that in childhood (between 8 and 12 years) there is a tendency towards being a morning type, whereas in adolescence and in the early adult phase, there is a tendency towards being an afternoon type, returning to the morning type tendency in old age. Researches made by Vančová, Jančoková, Palovičová, and Pivovarniček (2013), and by showed that more than 77.4% of female university students tend to be neither chronotype.…”
Section: Introductionmentioning
confidence: 99%